Macroepifauna móvil asociada a una pradera de Thalassia testudinum en la bahía Triganá, Golfo de Urabá, Colombia (2014)
The mobile macroepifauna associated to Thalassia testudinum meadow was studied in quadrants of 1m2 placed on two fringes (shallow water and deep water) of it in Triganá Bay, Gulf of Urabá, Colombia. The results showed significant differences in coverage, biomass and width of leaves of T. testudinum between fringes. A total of 879 macroinvertebrates were collected of 42 species. The most abundant species were Cerithium cf. eburneum, Nassarius vibex, Neritina virginea, Clibanarius cubensis and C. antillensis. Statistical analyzes showed no relationship between mobile fauna and meadow fringes and consequently their distribution and abundance did not depend on the structure of the prairie between fringes.